Mechanotransduction in skin wound healing and scar formation: Potential therapeutic targets for controlling hypertrophic scarring - Yin, Jiayi; Zhang, Shiming; Yang, Chao; Wang, Yan; Shi, Bing; Zheng, Qian; Zeng, Ni; Huang, Hanyao (Frontiers in Immunology, 2022)
Hypertrophic scarring (HTS) is a major source of morbidity after cutaneous injury. Recent studies indicate that mechanical force significantly impacts wound healing and skin regeneration which opens up a new direction to combat scarring. Hence, a thorough understanding of the underlying mechanisms is essential in the development of efficacious scar therapeutics. This review provides an overview of the current understanding of the mechanotransduction signaling pathways in scar formation and some strategies that offload mechanical forces in the wounded region for scar prevention and treatment.